EVALUASI KESESUAIAN LAHAN TANAMAN DURIAN (Durio zibethinus) DI DAERAH ALIRAN SUNGAI (DAS) DESA ARTAIN KECAMATAN ARANIO KABUPATEN BANJAR - Syahrul Ramadhan H; Yusanto Nugroho; Susilawati Susilawati (Jurnal Sylva Scienteae, 2023)
It is important to evaluate the type of watershed rehabilitation .plants. for land suitability to be able to see the level of life of these plants, such as durian (Durio zibethinus). This study aims to analyze the suitability of land for durian species for the rehabilitation of the Barito watershed, Artain Village, Aranio District, Banjar Regency. The unit of analysis for the biophysical aspect is the location/soil sample that has been determined. Research variables include land suitability class criteria at the semi-detailed level. The sampling technique used purposive sampling method amounted to 6 samples on a flat slope (0-8%). Land suitability for durian plantations on flat slopes (0-8%) including S3wrfn (marginally appropriate), with the land limiting factor being water availability (w) namely rainfall/year with a value of 2881.84 mm, root conditions (r) moderate soil drainage – moderate to slow and effective depth of 83-84 cm, nutrient retention (f) pH 4.90 – 5.81 and available nutrient (n) content of N, P2O5 and K2O is very low – low. The level of improvement efforts carried out for activities of making irrigation or irrigation channels with a light effort level, construction of drainage channels with a light effort level and widening of planting holes and drainage with a light effort level, lime application with a light effort level, application of N and Potassium fertilizers with a low level of effort light effort, so that with these various improvements in the Land Unit I (flat slope class) it can make the potential land suitability become S2 (quite suitable)Jenis tanaman rehabilitasi DAS penting untuk dilakukan evaluasi kesesuaian lahan untuk dapat melihat tingkat kehidupan tanaman tersebut, seperti tanaman durian (Durio zibethinus). Penelitian ini bertujuan menganalisis kesesuaian lahan terhadap jenis tanaman durian untuk Rehabilitasi DAS Barito Desa Artain Kecamatan Aranio Kabupaten Banjar. Unit analisis aspek biofisik adalah lokasi/sampel tanah yang telah ditetapkan. Variabel penelitian meliputi kriteria kelas kesesuaian lahan tingkat semi detil. Teknik pengambilan sampel menggunakan metode purposive sampling berjumlah 6 sampel pada kelerengan datar (0-8%).  Kesesuaian lahan tanaman durian pada kelerengan datar (0-8%) termasuk S3wrfn (sesuai marginal), lahan yaitu dengan nilai 2881.84 mm, kondisi perakaran (r) drainase tanah sedang – sedang sampai lambat dan kedalaman efektif 83-84 cm, retensi hara (f) pH 4.90 – 5.81 dan hara tersedia (n) kandungan N, P2O5 dan K2O ialah sangat rendah – rendah. Tingkat usaha perbaikan yang dilakukan untuk kegiatan pembuatan saluran irigasi atau pengairan dengan tingkat usaha ringan, pembangunan saluran drainase dengan tingkat usaha ringan dan pelebaran lubang tanam serta pendangiran dengan tingkat usaha ringan, kegiatan pemberian kapur dengan tingkat usaha ringan, pemberian pupuk N dan Kalium dengan tingkat usaha ringan, sehingga dengan berbagai perbaikan tersebut pada Unit Lahan I (kelas lereng datar) dapat menjadikan kesesuaian lahan potensial menjadi S2 (cukup sesuai).